Population pharmacokinetics and dose optimisation of ritonavir-boosted atazanavir in Thai HIV-infected patients - Punyawudho B. (2017)
© 2017 Elsevier B.V. and International Society of Chemotherapy There is evidence that Thai patients receiving standard doses of ritonavir (RTV)-boosted atazanavir (ATV/r) have high exposure to atazanavir (ATV) leading to a higher risk of toxicity. A lower dose of ATV/r may provide adequate exposure in this population. However, pharmacokinetic data on ATV/r in Thai patients required for dose adjustment are limited. This study aimed to develop a population pharmacokinetic model of ATV/r and to determine the influence of patient characteristics on ATV pharmacokinetics. Monte Carlo simulations were performed to estimate the proportion of patients achieving target ATV trough concentration (C trough ) with the standard ATV/r dose of 300/100 mg and a low dose of 200/100 mg once daily (OD). A total of 127 Thai HIV-infected patients were included in this study. One random blood sample was collected to determine ATV and RTV concentrations at each clinic visit from 100 patients. Intensive data from 27 patients enrolled in previous studies were also included. Data were analysed using the non-linear mixed-effects modelling approach. A one-compartment model with first-order absorption and elimination and absorption lag time best described the data. The population mean clearance of ATV/r was 4.93 L/h in female patients and was 28.7% higher in male patients. Simulation results showed a higher proportion of patients achieving ATV C trough within the target range with ATV/r 200/100 mg compared with 300/100 mg. The 200/100 mg OD dose of ATV/r provides adequate ATV exposure in Thai HIV-infected patients. Therefore, a lower dose of ATV/r should be considered for Thai and Asian populations.